PAI Terintegrasi Trauma Healing: Penguatan Karakter Islami Anak Korban Bencana di SDN 2 Tualang Cut Aceh Tamiang - Adrian Yudabangsa; Muhammad Ashadi Rasyad; Muhammad Furqan; Assya Syahnaz; Amirul Haq RD; Ammar Zaki; Helmi Ghoffar (Civiliza Publishing, 2026)
Aceh Tamiang Regency, especially Manyak Payed District, is one of the areas affected by the flood disaster that left a deep psychological impact on school-age children, including trauma, anxiety, and loss of motivation to learn. This community service activity aims to implement an integrated Islamic Religious Education (PAI) approach to trauma healing to strengthen Islamic character while supporting the psychosocial recovery of disaster victims at SDN 2 Tualang Cut, Aceh Tamiang. The program is implemented through three systematic stages, namely planning, implementation, and monitoring. The implementation stage includes five integrated activities, namely Islamic storytelling, light dialogue sessions, joint prayers, distribution of ATK packages and nutritious snacks, and creative expression. A total of 120 students in grades I, II, and III were involved in this program which was funded by the PKM Disaster Emergency Response Program of Samudra University. Data was collected through observation and interviews with classroom teachers and principals. The monitoring results showed significant positive changes in students' psychosocial conditions, where children who previously seemed moody and unmotivated became more cheerful, active in learning, and more socially interactive. These findings prove that the integration of PAI and trauma healing provides a holistic and effective approach in post-disaster recovery, touching the spiritual, emotional, and social dimensions of children at the same time, and has the potential to be a model that can be replicated by educational institutions in disaster-prone areas.